Targeting Thioredoxin-1 by dimethyl fumarate induces ripoptosome-mediated cell death - Schroeder, Anne; Nicolay, Jan Peter (Scientific reports, 2017)
Constitutively active NFκB promotes survival of many cancers, especially T-cell lymphomas and leukemias by upregulating antiapoptotic proteins such as inhibitors of apoptosis (IAPs) and FLICE-like inhibitory proteins (cFLIPs). IAPs and cFLIPs negatively regulate the ripoptosome, which mediates cell death in an apoptotic or necroptotic manner. Here, we demonstrate for the first time, that DMF antagonizes NFκB by suppressing Thioredoxin-1 (Trx1), a major regulator of NFκB transcriptional activity. DMF-mediated inhibition of NFκB causes ripoptosome formation via downregulation of IAPs and cFLIPs. In addition, DMF promotes mitochondrial Smac release and subsequent degradation of IAPs, further enhancing cell death in tumor cells displaying constitutive NFκB activity. Significantly, CTCL patients treated with DMF display substantial ripoptosome formation and caspase-3 cleavage in T-cells. DMF induces cell death predominantly in malignant or activated T-cells. Further, we show that malignant T-cells can die by both apoptosis and necroptosis, in contrast to resting T-cells, which are restricted to apoptosis upon DMF administration. In summary, our data provide new mechanistic insight in the regulation of cell death by targeting NFκB via Trx1 in cancer. Thus, interference with Trx1 activity is a novel approach for treatment of NFκB-dependent tumors.